A public resource of baseline data from the api autosomal dominant alzheimer’s disease colombia trial (2018)
ABSTRACT: The Alzheimer’s Prevention Initiative (API) was established to accelerate Alzheimer’s disease (AD) prevention research, forge public-private partnerships, conduct prevention tri- als with maximal scientific benefit, clarify biomarker roles, and share data and biological samples after trials are completed. In conjunction with the Collaboration for Alzheimer’s Prevention (CAP), API also agreed to share baseline data before its trials arecompleted. We now report availability of baseline data and brain images from the API Autosomal Dominant AD (ADAD) Colombia Trial, a prevention trial in Presenilin 1 (PSEN1) E280A mutation carriers and non-carriers from the world’s largest ADAD kindred. Methods: The API ADAD Colombia Trial is a 60-month randomized, placebo-controlled prevention trial of the investigational amyloid-b (Ab) antibody therapy crenezumab in 252 unimpaired 30- 60 year-old kindred members, including mutation carriers who were randomized to active treatment or placebo and non-carriers who receive placebo. The mutation is virtually certain to cause mild cognitive impairment (MCI) and dementia due to AD at respective the ages of 4465 and 4965. For ethical reasons, participants have not received their mutation test results. Florbetapir (Ab) PET, fluorodeoxyglucose PET, and MRI scans—and CSF and blood samples in those who consent–are acquired at baseline and several follow-up visits. GTP1 (tau) PET scans are proposed at wmonths 30 and 60. The baseline data-sharing plan was developed to benefit the field while protecting participant identification and trial integrity. Several data attributes and information about how to request data will be available through the Global Alzheimer’s Association Interactive Network (GAAIN). Subject-level data and images will be then shared with approved users. Other data and available biological samples will be shared after the trial is completed. Results:We will summarize participant characteristics, our available data and data-sharing plan, and how researchers can request and receive data. Conclusions: The API ADAD Colombia Trial baseline data sharing program is intended to advance the study of preclinical AD, underscore the importance of data sharing in all trials, and do so in a way that protects participant identification and trial integrity.